The Potential Antibacterial Power of Ethanol Extract of Durian Peel (Durio zibethinus murr) Against Enterococcus faecalis - Aurelia Maulini Rizky; Danica Anastasia; Listia Eka Merdekawati (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2020)
Durian (Durio zibethinus murr) is a fruit with the 4th commodity in Indonesia where the skin has antibacterial properties. Durian peel contains active substances in the form of flavonoids, alkaloids, saponins, tannins, and triterpenoids which have significant antibacterial activity against Gram-positive bacteria such as Enterococcus faecalis. This study aimed to determine the antibacterial activity of the ethanol extract of durian peel against Enterococcus faecalis bacteria. Methods: This was quasi-experimental using post-test only control group design with 4 treatment groups consisting of ethanol extract of durian peel with concentrations of 10%, 15%, 20%, 25% and 2% chlorhexidine as a control group with 6 repetitions. The antibacterial activity was tested using the agar diffusion method Kirby-Bauer discs with Mueller Hinton Agar media. All groups were assessed after 24 hours of incubation period at 37°C. The diameter of the inhibition zone was calculated using a caliper and the data were analyzed using the One Way ANOVA test and the Post Hoc Games Howel test. Results: There was a significant difference in the antibacterial activity of the ethanol extract of durian peel against Enterococcus faecalis between all groups except in the concentration groups of 25% and 20% as well as 15% and 10%. The higher concentration of extract formed a larger clear zone. Conclusion: the ethanol extract of durian peel concentrations of 25%, 20%, 15% and 10% have antibacterial power against Enterococcus faecalis bacteria with an average of 1.69 mm, 1.25 mm, 0.78 mm and 0.42 mm which are classified as weak category.